2012
DOI: 10.1890/11-1912.1
|View full text |Cite
|
Sign up to set email alerts
|

Phenological tracking enables positive species responses to climate change

Abstract: Abstract. Earlier spring phenology observed in many plant species in recent decades provides compelling evidence that species are already responding to the rising global temperatures associated with anthropogenic climate change. There is great variability among species, however, in their phenological sensitivity to temperature. Species that do not phenologically ''track'' climate change may be at a disadvantage if their growth becomes limited by missed interactions with mutualists, or a shorter growing season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
256
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(267 citation statements)
references
References 38 publications
8
256
1
2
Order By: Relevance
“…These phenological shifts are generally attributed to warming, which is typically more pronounced at higher altitudes (28). The capacity of species to adapt their phenology to climate change is important for their survival, in particular when species are unable to migrate to other habitats with suitable climate (29). Studies have shown that variation in phenology allows for the coexistence of species through temporal complementarity (30).…”
Section: Discussionmentioning
confidence: 99%
“…These phenological shifts are generally attributed to warming, which is typically more pronounced at higher altitudes (28). The capacity of species to adapt their phenology to climate change is important for their survival, in particular when species are unable to migrate to other habitats with suitable climate (29). Studies have shown that variation in phenology allows for the coexistence of species through temporal complementarity (30).…”
Section: Discussionmentioning
confidence: 99%
“…We found that especially higher nitrogen and potassium content were linked to stronger phenological shifts as well as higher Δ 13 C and thus lower water‐use efficiency. Nitrogen, being related to enzyme content and photosynthesis rates (Bucher et al., 2018; Evans, 1989), had highest importance for the ability to shift FFD which strengthens the claim of shifts in FFD being directly related to plant performance (Cleland et al., 2012; Willis et al., 2008). In our study, we found that SLA was related to less pronounced shifts in FFD which is opposing findings by König et al.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in flowering phenology might, however, lead to increased fecundity if there is no mismatch with pollinating insects (Baeten, Sercu, Bonte, Vanhellemont, & Verheyen, 2015; Sparks, Jeffree, & Jeffree, 2000). Overall, studies confirmed that the performance and abundance of species with an advanced phenology increased, whereas the performance of the others decreased (Baeten et al., 2015; Cleland et al., 2012; Hulme, 2011; Willis, Ruhfel, Primack, Miller‐Rushing, & Davis, 2008). Studies conducted along elevational gradients found significant changes in leaf phenology of tree species and species‐specific differences in temperature sensitivity (Schuster, Estrella, & Menzel, 2014; Schuster, Kirchner, Jakobi, & Menzel, 2014; Vitasse, Porté, et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies make it abundantly clear that ongoing climatic warming has affected the phenology (Parmesan and Yohe 2003, Menzel et al 2006, Parmesan 2006, Amano et al 2010, Morin et al 2010, performance (Rossi et al 2004, Cleland et al 2012, and distributions (Parmesan and Yohe 2003, Walther 2010, Chen et al 2011) of species, less appreciated is the fact that climatic change might also alter both intra-and interspecific interactions (Tylianakis et al 2008). Predictions related to the effects of ongoing climatic change largely consider the direct effects of climate on species without taking into account how interactions between species might also affect their responses to climatic change (Davis et al 1998, Araú jo and Rahbek 2006, Buckley et al 2010.…”
Section: Introductionmentioning
confidence: 99%